DISTORSI PEMAKNAAN LAFADZ SHAHIBU MAKS ANTARA PETUGAS PEMUNGUT PAJAK DAN PUNGUTAN LIAR - Ana Fadhilah (Postgraduate State Islamic Institute (IAIN) Metro, 2018)
The biggest source of income for the country in Indonesia comes from taxes. The tax function is vital for the success of the country's development. However, in its management, tax officials were very vulnerable to being involved in fraud cases which resulted in a decline in public confidence, leading to a discourse on tax boycott initiated by one of the religious activists (Islam). They assume that all absolute tax employees are rewarded for hell, based on the hadith narrated from Uqbah